2021
DOI: 10.21109/kesmas.v16i1.3271
|View full text |Cite
|
Sign up to set email alerts
|

Low Knowledge and Lack of Awareness Regarding the Mass Drug Administration Health Promotion as the Determinant Factors in Non-Compliance to the Mass Drug Administration Health Program

Abstract: From the total population of the community in Kuningan District, 78.61% were taking filariasis drugs in the Mass Drug Administration (MDA) program in 2017. Cilimus Subdistrict became a filariasis-endemic area in Kuningan with 72.39% of the MDA program coverage in 2017 (government target >86%). The purpose of this study was to analyze the determinant factors of compliance with the MDA program. The study was an analytical study with a cross-sectional design and conducted from May to June 2018. The sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(32 reference statements)
1
1
0
1
Order By: Relevance
“…24 This is in accordance with the research conducted by Annashr et al in Cilimus District, Kuningan Regency, where it was found that family support had a significant effect on adherence to filariasis prevention treatment (p = 0.016). 25 This is also in line with research conducted by Rosanti et al in Pabean, Pekalongan City, which stated that the presence of a drug-taking supervisor from the family environment was the most important variable in improving medication adherence 26 in the work area. Research by Iwan et al in the working area of Waihaong and Air Salobar Health Centers, Ambon City, stated that the support from people around showed an important role in adherence to medication.…”
Section: Resultssupporting
confidence: 84%
“…24 This is in accordance with the research conducted by Annashr et al in Cilimus District, Kuningan Regency, where it was found that family support had a significant effect on adherence to filariasis prevention treatment (p = 0.016). 25 This is also in line with research conducted by Rosanti et al in Pabean, Pekalongan City, which stated that the presence of a drug-taking supervisor from the family environment was the most important variable in improving medication adherence 26 in the work area. Research by Iwan et al in the working area of Waihaong and Air Salobar Health Centers, Ambon City, stated that the support from people around showed an important role in adherence to medication.…”
Section: Resultssupporting
confidence: 84%
“…Travel time to the MDA distribution site was only collected by one study, delineating an individual’s will to take MDA, with the practicality of doing so (AOR 0.22 (95% CI: 0.14–0.35) >60 minutes, AOR 0.08 (95% CI: 0.04–0.17) 30–60 minutes), reference: < 30 minutes) [ 58 ]. Participant comprehension of parasitic disease (AOR 13.68 (95% CI: 1.65–113.57)) [ 59 ], or the purpose of MDA (AOR 2.27 (95% CI: 1.44–3.59)) [ 58 ] was noted to be significant. Similarly, internal cues to action such as the assumption of own infection status, susceptibility of disease and fear of disease was shown to be significant (AOR 3.628 (95% CI: 1.96–6.73)) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian lain juga menyebutkan dukungan keluarga merupakan salah satu faktor yang berhubungan dengan kepatuhan minum obat filariasis. Karena keluarga umumnya dekat satu sama lain dan memiliki pengaruh besar dalam pengambilan keputusan, selain itu keluarga juga dapat menjadi lingkungan yang efektif dalam membagikan pengetahuan tentang filariasis 41 . Penelitian yang dilakukan oleh Krentel, dkk, menyatakan bahwa komunitas atau lingkungan sosial mengambil peran penting dalam keberhasilan program kesehatan global, termasuk POPM filariasis.…”
Section: Faktor Eskternal Yang Berhubungan Dengan Kepatuhan Minum Obatunclassified